2016
DOI: 10.1002/lary.25946
|View full text |Cite
|
Sign up to set email alerts
|

Diverse clinical and laboratory manifestations of bilateral vestibulopathy

Abstract: 4. Laryngoscope, 127:E42-E49, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…Positive bilateral vHIT does not always correlate with caloric or rotatory chair test results in BV. This indicates that a spectrum of vestibulopathies exists according to the stimulation frequency of the deficit [79].…”
Section: Bilateral Vestibular (Bv) Failurementioning
confidence: 90%
“…Positive bilateral vHIT does not always correlate with caloric or rotatory chair test results in BV. This indicates that a spectrum of vestibulopathies exists according to the stimulation frequency of the deficit [79].…”
Section: Bilateral Vestibular (Bv) Failurementioning
confidence: 90%
“…Furthermore, the positive correlation between average vHIT gain and average rotary chair gain suggests that average vHIT gain in can be used to determine level of severity. This contrasts Moon et al 21 who identified 65 patients with bilateral vHIT abnormalities by either gain reduction or observable corrective saccade. Using ROC curves, they found no consistency between caloric testing, vHIT, and rotary chair for diagnosing BVH.…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, Weber et al 6 demonstrated good agreement between vHIT gain and caloric responses in patients with BVH due to gentamicin vestibulotoxicity, where patients with average vHIT gains less than 0.3 were unresponsive to caloric testing. Moon et al 21 also noted increasing average vHIT gain in patient groups as their caloric responses improved from bilateral to unilateral to normal.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Chronic vestibular insufficiency can be due to severe unilateral [127, 128] or moderate, symmetrical or asymmetrical, bilateral vestibular impairment [129, 130]. The patient with chronic vestibular insufficiency has no symptoms while sitting or lying but feels off-balance as soon as she stands and more so when she walks [131].…”
Section: Video Head Impulse Testingmentioning
confidence: 99%